Ectonucleotidases in Blood Malignancies: A Tale of Surface Markers and Therapeutic Targets - Vaisitti, Tiziana; Arruga, Francesca; Guerra, Giulia; Deaglio, Silvia (Frontiers in Immunology, 2019)
Leukemia develops as the result of intrinsic features of the transformed cell, such as gene mutations and derived oncogenic signaling, and extrinsic factors, such as a tumor-friendly, immunosuppressed microenvironment, predominantly in the lymph nodes and the bone marrow. There, high extracellular levels of nucleotides, mainly NAD+ and ATP, are catabolized by different ectonucleotidases, which can be divided in two families according to substrate specificity: on one side those that metabolize NAD+, including CD38, CD157 and CD203a; on the other, those that convert ATP, namely CD39 (and other ENTPDases) and CD73. They generate products that modulate intracellular calcium levels and that activate purinergic receptors. They can also converge on adenosine generation with profound effects, both on leukemic cells, enhancing chemoresistance and homing, and on non-malignant immune cells, polarizing them towards tolerance. This review will first provide an overview of ectonucleotidases expression within the immune system, in physiological and pathological conditions. We will then focus on different hematological malignancies, discussing their role as disease markers and possibly pathogenic agents. Lastly, we will describe current efforts aimed at therapeutic targeting of this family of enzymes.